Using the Internet - DK Publishing, Inc. (New York : DK, 1997)
A step-by-step guide to understanding and using the Internet, revealed through 101 tips that provide information on jargon, modems, e-mail, downloading files, Telnet, newsgroups, chat rooms, and other aspects of the world-wide system.
The Science Teacher (N.S.T.A.).
Young Adult
Keywords: Internet; Internet